2023
DOI: 10.3346/jkms.2023.38.e108
|View full text |Cite
|
Sign up to set email alerts
|

Recent Prevalence of and Factors Associated With Chronic Obstructive Pulmonary Disease in a Rapidly Aging Society: Korea National Health and Nutrition Examination Survey 2015–2019

Abstract: Background The prevalence of chronic obstructive pulmonary disease (COPD) increases with age, and aging is an important risk factor for COPD development. In the era of global aging, demographic information about the prevalence of and factors associated with COPD are important to establish COPD care plans. However, limited information is available in rapidly aging societies, including Korea. Methods We conducted a cross-sectional observational study using Korea National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
(52 reference statements)
1
14
0
Order By: Relevance
“… 5 Across all age groups (40–49, 50–59, 60–69, and ≥ 70 years), the highest prevalence of COPD was observed in patients aged ≥ 70 years (30.4%), with the prevalence also being higher in males than females (19.9% vs. 6.4%). 5 Based on longitudinal data from the National Health Insurance Service (NHIS), a key institution that provides healthcare insurance to all citizens in South Korea, 6 the 5-year mortality of Korean patients with COPD was 25.4%, and this increased rapidly with age. 7 Overall, COPD exerts a substantial socioeconomic burden in South Korea 8 and ranks as the third leading cause of total disability-adjusted life years, accounting for 6.2% of the burden associated with non-communicable diseases.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“… 5 Across all age groups (40–49, 50–59, 60–69, and ≥ 70 years), the highest prevalence of COPD was observed in patients aged ≥ 70 years (30.4%), with the prevalence also being higher in males than females (19.9% vs. 6.4%). 5 Based on longitudinal data from the National Health Insurance Service (NHIS), a key institution that provides healthcare insurance to all citizens in South Korea, 6 the 5-year mortality of Korean patients with COPD was 25.4%, and this increased rapidly with age. 7 Overall, COPD exerts a substantial socioeconomic burden in South Korea 8 and ranks as the third leading cause of total disability-adjusted life years, accounting for 6.2% of the burden associated with non-communicable diseases.…”
Section: Introductionmentioning
confidence: 90%
“…2 3 4 Analysis of data from the Korea National Health and Nutrition Examination Survey (KNHANES) between 2015 and 2019 revealed that the overall prevalence of COPD in South Korea was 12.9%. 5 Over the 5-year survey period, the annual prevalence of COPD remained constant, ranging between 11.5% and 13.6%. 5 Across all age groups (40–49, 50–59, 60–69, and ≥ 70 years), the highest prevalence of COPD was observed in patients aged ≥ 70 years (30.4%), with the prevalence also being higher in males than females (19.9% vs. 6.4%).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…1 Globally, the disease burden of COPD is expected to increase in the future due to continued exposure to COPD risk factors and world population aging. 2 3 Apart from smoking and air pollution, a history of respiratory infections is now recognized as an important but underrecognized etiology of COPD 4 5 that should be managed properly.…”
Section: Introductionmentioning
confidence: 99%
“…The concept that a previous pulmonary tuberculosis (TB) history is associated with the development of chronic airway obstruction is now well established. 3 4 5 6 7 8 9 Particularly, it has been reported that the risk of COPD is up to 3 times higher in patients with a previous TB diagnosis than in those without a previous TB diagnosis. 8 9 Even after successful TB treatment, a considerable proportion of survivors from TB (TB survivors) suffer from impairment of pulmonary function and persistent pulmonary inflammation.…”
Section: Introductionmentioning
confidence: 99%